A Spectrum of Descending Thoracic Aorta Diameter Measurement on Computerized Tomography: A Report of 500 Sudanese Patients - Hanan Elnour, Amin Elzaki (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The clinical show of illnesses including the thoracic aorta goes from countless patients who have no symptoms, having a medically imperceptible thoracic part of the Arora to victims with side effects of extreme ribcage torment because of intense aortic analysis. Objective: A retrospective study was conducted in computed tomography CT departments of three hospitals to quantify the average thoracic aorta width in the population of Sudan to compare it with international measurements. Methodology: The data collected from 500 randomly selected non-pathological patients were analyzed by the SPSS program and presented in tables and figures. Results: Results revealed that the diameter of the aorta is affected by the body length, age of the patient, and weight, except the gender which is a non-significant factor. Also, the typical size of the plunging part of the Aorta was 12.17±1.78 cm, the proximal diameter of the aorta was 2.51±0.56 cm, the focus width was 2.08±0.41 cm, and the distal breadth was 2.11±0.45 cm. The width of the aorta is very susceptible to size as well as out of the individual. Furthermore, an unusually large distinction (P=0.001) was seen between age and distant breadth of the aorta, although a small distinction (P=0.018) was obtained between the patient’s level and terminal breadth of the aortic arch. Conclusion: It is reasoned that the figured tomography is assuming an extraordinary part in the estimation of the ordinary width of slipping of the thoracic aorta by giving a subtle depiction of sliding thoracic aorta breadth in a gathering of the solid Sudanese populace.